Universal Electrification Development Strategies for Ethiopia - Mondal, Alam (2018)
Presented by Alam Hossain Mondal, research fellow, International Food Policy Research Institute (IFPRI), at the policy workshop on alternative pathways to improve electricity access in Ethiopia, Addis Ababa, Ethiopia, on May 2, 2018.